Assessment of sperm DNA in patients submitted the assisted reproduction technology procedures - Tsuribe, Patricia Miyuki; Lima Neto, Joao Ferreira [UNESP]; Golim, Marjorie de Assis [UNESP]; Freitas Dell'Aqua, Camila de Paula [UNESP]; Issa, Joao Paulo; Monte Gobbo, Carlos Alberto [UNESP] (Soc Brasileira Reproducao Assistida-sbra, 2016)
Objective: This study aimed to produce data on sperm quality while maintaining the integrity of sperm DNA samples taken from patients submitted to in vitro fertilization (IVF) procedures at our center, and determine whether increased levels of histones were associated with sperm DNA damage and decreased fertilization, cleavage, and pregnancy rates. Such findings might shed light on the physiology and outcomes of pregnancy. Methods: Semen samples from 27 patients divided into two groups were analyzed. The case group included individuals offered IVF; the control group had subjects with normal spermograms. Sperm DNA structure was assessed through phosphorylated histone H2AX analysis by flow cytometry. Results: The patients with altered sperm parameters had more histones in sperm chromatin than the individuals with normal sperm parameters. Conclusion: Results indicated that increased levels of histone in sperm chromatin do not affect embryo production, but affect the cleavage rate, embryo quality, and might thus reduce pregnancy rates. The integrity of the paternal genome is of paramount importance in the initiation and maintenance of a viable pregnancy in patients treated with assisted reproduction technology procedures. Further studies on sperm diagnostic tests at a nuclear level might improve the treatment offered to infertile couples.
Keywords: Sperm DNA; Histones; Pregnancy; Fertilization rate; ICSI